b urposes, problems, and possibilities /c - Ross, E. Wayne (b, 2014)
The Social Studies Curriculum, Fourth Edition updates the definitive overview of the issues teachers face when creating learning experiences for students in social studies. The book connects the diverse elements of the social studies curriculum$1 (Bcivic, global, social issues$1 (Boffering a unique and critical perspective that separates it from other texts. Completely updated, this book includes twelve new chapters on the history of the social studies; democratic social studies; citizenship education; anarchist inspired transformative social studies; patriotism; ecological democracy; Native studies; inquiry teaching; Islamophobia; capitalism and class struggle; gender, sex, sexuality, and youth experiences in school; and critical media literacy. All the chapters from the previous edition have been thoroughly revised and updated, including those on teaching social studies in the age of curriculum standardization and high-stakes testing, critical multicultural social studies, prejudice and racism, assessment, and teaching democracy. Readers are encouraged to reconsider their assumptions and understanding about the origins, purposes, nature, and possibilities of the social studies curriculum.s
Includes bibliographical references and index.
Keywords: Social sciences -- Study and teaching(Elementary) -- Curricula -- United States; Social sciences -- Study and teaching(Secondary) -- Curricula -- United States; Curriculum planning -- United States